Adjuvant Ciprofloxacin for Persistent BK Polyomavirus Infection in Kidney Transplant Recipients - David Arroyo; Sindhu Chandran; Parsia A. Vagefi; David Wojciechowski (Journal of Transplantation)
Background. BK virus (BKV) infection is a common complication following kidney transplantation. Immunosuppression reduction is the cornerstone of treatment while adjuvant drugs have been tried in small uncontrolled studies. We sought to examine our center’s experience with the use of ciprofloxacin in patients with persistent BKV infection. Methods. Retrospective evaluation of the effect of a 30-day ciprofloxacin course (250 mg twice daily) on BKV infection in kidney transplant recipients who had been diagnosed with BK viruria ≥106 copies/mL and viremia ≥500 copies/mL and in whom the infection did not resolve after immunosuppression reduction and/or treatment with other adjuvant agents. BKV in plasma and urine was evaluated after 3 months following treatment with ciprofloxacin. Results. Nine kidney transplant recipients received ciprofloxacin at a median of 130 days following the initial reduction in immunosuppression. Three patients showed complete viral clearance and another 3 had a ≥50% decrease in plasma viral load. No serious adverse events secondary to ciprofloxacin were reported and no grafts were lost due to BKV up to 1 year after treatment. Conclusion. Ciprofloxacin may be a useful therapy for persistent BKV infection despite conventional treatment. Randomized trials are required to evaluate the potential benefit of this adjuvant therapy.